The praise of non-beings - Hovey, Craig (Theology, 2011)
Christian theology has said much about existence and being – whether God’s being is the same as that of creatures, whether existence is good or morally neutral, and whether we can say anything meaningful about how God relates to things that do not exist. This article sketches an outline of some of these difficult concepts with an eye to understanding them better, where the possible tensions lie, and why they matter. In particular, it looks to theologians such as Dionysius, Thomas Aquinas and others who not only push the question of whether God’s transcendence of being has implications for the things that God has created, but even dare to ask about non-beings.